2021
DOI: 10.3390/antiox10030406
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Vascular Damage in the Context of Obesity: The Hidden Guest

Abstract: The vascular system plays a central role in the transport of cells, oxygen and nutrients between different regions of the body, depending on the needs, as well as of metabolic waste products for their elimination. While the structure of different components of the vascular system varies, these structures, especially those of main arteries and arterioles, can be affected by the presence of different cardiovascular risk factors, including obesity. This vascular remodeling is mainly characterized by a thickening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 236 publications
(171 reference statements)
0
21
0
15
Order By: Relevance
“…The renin-angiotensin system (RAS) plays an important pathophysiological role. The production of RAS components by adipocytes is exacerbated during obesity, contributing to the systemic RAS which then affects the cardiovascular system (171). The up-regulation of adipose RAS, and especially the increase of angiotensin II production, promotes inflammation through increased chemokine production, oxidative stress and fibrosis (171).…”
Section: Oxidative Stress Endothelial Dysfunction and The Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The renin-angiotensin system (RAS) plays an important pathophysiological role. The production of RAS components by adipocytes is exacerbated during obesity, contributing to the systemic RAS which then affects the cardiovascular system (171). The up-regulation of adipose RAS, and especially the increase of angiotensin II production, promotes inflammation through increased chemokine production, oxidative stress and fibrosis (171).…”
Section: Oxidative Stress Endothelial Dysfunction and The Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…The production of RAS components by adipocytes is exacerbated during obesity, contributing to the systemic RAS which then affects the cardiovascular system (171). The up-regulation of adipose RAS, and especially the increase of angiotensin II production, promotes inflammation through increased chemokine production, oxidative stress and fibrosis (171). Conversely, blocking or preventing RAS activation in AT can reduce oxidative stress, improve insulin resistance and reduce inflammation (173,174).…”
Section: Oxidative Stress Endothelial Dysfunction and The Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%
“…The above reactions show the endogenous antioxidants undergoing reduction by scavenging the free radicals and inhibiting them from reacting with the other important biological molecules. Furthermore, it was observed that nicotinamide adenine-dinucleotide phosphate, NADPH, which is required to reduce the levels of oxidized glutathione decreases during metabolic diseases, aging, and oxidative stress [39][40][41], like the decrease in endogenous defense molecules, such as thiols and SOD promotes fibrosis [42].…”
Section: Figurementioning
confidence: 99%
“…For minor vascular damage clinically, simple surgical sutures and medical treatment can be used for treatment. However, severe trauma or insufficient blood supply caused by large-scale defects can cause serious consequences, such as claudication, sores, organ dysfunction, necrosis, or even death [ 4 , 5 , 6 ]. At present, vascular grafts are widely used clinically to prevent severe vascular injury, such as polyurethane [ 7 ], polyester [ 8 ], expanded polytetrafluoroethylene (ePTFE) [ 9 ], etc.…”
Section: Introductionmentioning
confidence: 99%